Análise da estimulação cognitiva e de seus ruídos com base no EEG - Magalhães, Kaliny Alice Carvalho de Oliveira (2023)
The processes of the mind generate sensations such as anger, excitement, and happiness. The EEG is one of the main study tools when it comes to analyzing the behavior of the electrical activity of the cerebral cortex. Despite being widely used, it is necessary to analyze all levels when it comes to a powerful exam like this. Cognitive processes and musical stimulation are protocols for evaluating the functioning of the EEG tracing that allow observing changes at different levels. In addition, as it is an exam that suffers a lot of external influence, it is essential to study noise in its tracing, making it necessary to create ways to reduce these artifacts in the signal, therefore, a eletromagnetically shielded room is a safe way to follow. Noise reduction is crucial, since the EEG is one of the most used tests in the Brain Death protocol, that is, the more information that is filtered correctly, the better the degree of its evaluation. Therefore, musical stimulation and cognitive processes have shown that they directly interfere with some brain rhythms, causing evident alterations and oscillations. Eletromagnetically shielded rooms work more assertively when higher sampling frequencies are used.